Impact of coronary anatomy and stenting technique on long-term outcome after drug-eluting stent implantation for unprotected left main coronary artery disease - Tiroch, Klaus; Mehilli, Julinda; Byrne, Robert A.; Schulz, Stefanie; Massberg, Steffen; Laugwitz, Karl-Ludwig; Vorpahl, Marc; Seyfarth, Melchior; Kastrati, Adnan (Jacc-Cardiovascular Interventions, 2014)
Objectives This study sought to evaluate the impact of anatomic and procedural variables on the outcome of the unprotected left main coronary artery (uLMCA) itself after drug-eluting stent (DES) implantation. Background There is a controversial debate regarding when and how to perform percutaneous coronary intervention (PCI) for an uLMCA stenosis. Methods This analysis is based on a randomized study of 607 patients undergoing PCI for uLMCA, randomized 1:1 to receive paclitaxel- or sirolimus-eluting stents. We evaluated the impact of the SYNTAX score, uLMCA anatomy, and stenting technique on in-stent restenosis (ISR), target lesion revascularization (TLR), and the 3-year outcomes. Results The 3-year cardiac mortality rate was 5.8%; 235 (39%) patients had a true bifurcation lesion (TBL), and the median SYNTAX score was 27. TBL was associated with a higher need for multiple stents (72% vs. 37%, p < 0.001). TBL was a significant predictor of ISR (23% vs. 14%, p = 0.008) and for TLR (18% vs. 9%, p < 0.001). The need for multiple stents was a predictor of ISR (22% vs. 13%, p = 0.005) and for TLR (16% vs. 9%, p = 0.005). Culotte stenting showed better results compared with T-stenting for ISR (21% vs. 56%, p = 0.02) and for TLR (15% vs. 56%, p < 0.001). We observed a significant association between uLMCA-TLR and SYNTAX scores (9.2% for scores ≤22, 14.9% for scores 23 to 32, and 13.0% for scores ≥33, p = 0.008). Conclusions PCI of uLMCA lesions with DES is safe and effective out to 3 years. TBL and multiple stents were independent predictors for ISR. In the multivariate analysis, independent predictors for TLR were TBL, age, and EuroSCORE (European System for Cardiac Operative Risk Evaluation). (Drug-Eluting-Stents for Unprotected Left Main Stem Disease [ISAR-LEFT-MAIN]; NCT00133237). © 2014 by the American College of Cardiology Foundation.
CRIS-Team Scopus Importer:2023-03-08
Keywords: left main; stenting technique; SYNTAX score